2022
DOI: 10.1371/journal.pcbi.1010065
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and clustering of kinase isoform expression in metastatic melanoma

Abstract: Mutations to the human kinome are known to play causal roles in cancer. The kinome regulates numerous cell processes including growth, proliferation, differentiation, and apoptosis. In addition to aberrant expression, aberrant alternative splicing of cancer-driver genes is receiving increased attention as it could lead to loss or gain of functional domains, altering a kinase’s downstream impact. The present study quantifies changes in gene expression and isoform ratios in the kinome of metastatic melanoma cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 84 publications
3
1
0
Order By: Relevance
“…Comparing to other TCGA-based clustering schemes with variation of information (VoI) analysis (see Methods), we observed the strongest concordance of our Isoform clustering scheme with cancer type and mRNA, followed by miRNA and iCluster (Figure 1G). The VoI analysis further shows that the gene isoform expression provides higher resolution of cancer type classification compared to mRNA at the gene level (1.6 vs. 2.1 in VoI), which is consistent with our previous finding that the differential isoform ratio has little correlation with the differential expression at gene level in the human kinome in SKCM cancer [4].…”
Section: Gene Isoform Expression and Somatic Mutation Profiles Provid...supporting
confidence: 91%
See 1 more Smart Citation
“…Comparing to other TCGA-based clustering schemes with variation of information (VoI) analysis (see Methods), we observed the strongest concordance of our Isoform clustering scheme with cancer type and mRNA, followed by miRNA and iCluster (Figure 1G). The VoI analysis further shows that the gene isoform expression provides higher resolution of cancer type classification compared to mRNA at the gene level (1.6 vs. 2.1 in VoI), which is consistent with our previous finding that the differential isoform ratio has little correlation with the differential expression at gene level in the human kinome in SKCM cancer [4].…”
Section: Gene Isoform Expression and Somatic Mutation Profiles Provid...supporting
confidence: 91%
“…Aberrant AS is common in human cancers and affects cancer progression in many aspects known as the 'hallmarks of cancer' [2][3][4]. Somatic disease-causing mutations, or driver mutations, are commonly assumed to exert their effects by altering amino acid sequences, which eventually impairs the normal function of a protein [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this exon skipping may lead to reduced SLK activity and decreased apoptosis to facilitate tumor progression. Consistently, a recent analysis of RNASeq data from melanoma tumors has shown that expression of the long isoform is decreased whereas the short isoform is increased in metastatic tumors compared with primary tumors, suggesting a role of the exon skipping in facilitating metastasis 31 . Transferrin is another gene found to be correlated with poor prognosis at the SEPEP level but not gene level.…”
Section: Discussionsupporting
confidence: 62%
“…Therefore, this exon skipping may lead to reduced SLK activity and decreased apoptosis to facilitate tumor progression. Consistently, a recent analysis of RNASeq data from melanoma tumors has shown that expression of the long isoform is decreased, whereas the short isoform is increased in metastatic tumors compared with primary tumors, suggesting a role of the exon skipping in facilitating metastasis 38 . Transferrin is another gene found to be correlated with poor prognosis at the SEPEP level but not gene level.…”
Section: Discussionsupporting
confidence: 61%